Exploring the Pathogenic Mechanisms of West African Zika Virus : viral Replication and Host Interaction - (:unkn) unknown (My University, 2024)
The Zika virus (ZIKV), historically confined to Africa and Asia, has become a significant global health concern, especially after recent outbreaks in the Americas linked to severe congenital malformations and neurological disorders. While much research has focused on the Asian/American ZIKV genotype, evidence suggests that African ZIKV strains might also pose a serious threat to public health, particularly regarding fetal pathogenicity. This thesis aims to enhance our understanding of the molecular mechanisms underlying the pathogenicity of contemporary ZIKV strains from West Africa, focusing on nonstructural proteins involved in viral replication, immune evasion, and the host cell stress response.To achieve this, we generated an infectious molecular clone, GUINEA-18, from a ZIKV strain (ZIKV-15555) isolated in Guinea in 2018. This clone represents a contemporary African ZIKV strain. We compared it with the infectious molecular clone of the historical African ZIKV strain MR766, designated MR766MC. The replication properties of both viral clones were examined in VeroE6, A549, and HCM3 cells. GUINEA-18 exhibited a slower replication rate, reduced cytotoxicity, and a lower ability to activate the host’s innate immune system compared to MR766MC, suggesting different interactions with host cells.To dissect these differences, we created chimeric viruses by swapping nonstructural protein-coding regions between GUINEA-18 and MR766MC. Results highlighted the critical roles of NS1 to NS4B proteins in replication efficiency and pathogenicity, with NS4B being crucial for GUINEA-18’s replication properties. GUINEA-18 also developed an efficient mechanism to inhibit the assembly of cytoplasmic stress granules (SGs) in A549 cells, a defense mechanism typically triggered by viral infection. The ability of GUINEA-18 to block SG formation depended on the NS1 to NS4B proteins, underscoring their role in evading host defenses.Further investigation into the NS1 protein
Keywords: African Research